2013
DOI: 10.1152/japplphysiol.00599.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine and/or nasal CPAP treatment on laryngeal chemoreflexes in preterm lambs

Abstract: Current knowledge suggests that laryngeal chemoreflexes (LCR) are involved in the occurrence of certain neonatal apneas/bradycardias, especially in the preterm newborn. While caffeine and/or nasal continuous positive airway pressure (nCPAP) are the most frequent options used for treating apneas in preterm newborns, their effects on LCR-related apneas/bradycardias are virtually unknown. The aim of the present study was to test the hypothesis that caffeine and/or nCPAP decreases LCR-related cardiorespiratory inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Of note, the laryngeal chemoreflexes have been involved in some cases of apnea of prematurity, apparent life-threatening events in infancy and sudden infant death syndrome [20][22]. Of particular interest, we previously showed that nCPAP significantly decreases the cardiorespiratory inhibition observed during experimentally-induced laryngeal chemoreflexes in preterm lambs [23]. The present results fittingly complement the findings of the former study, showing that nCPAP not only decreases the number of GER reaching the proximal esophagus (and thus potentially the laryngeal mucosa), but also prevents the potentially dramatic cardiorespiratory consequences of laryngeal chemoreflexes in newborns.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, the laryngeal chemoreflexes have been involved in some cases of apnea of prematurity, apparent life-threatening events in infancy and sudden infant death syndrome [20][22]. Of particular interest, we previously showed that nCPAP significantly decreases the cardiorespiratory inhibition observed during experimentally-induced laryngeal chemoreflexes in preterm lambs [23]. The present results fittingly complement the findings of the former study, showing that nCPAP not only decreases the number of GER reaching the proximal esophagus (and thus potentially the laryngeal mucosa), but also prevents the potentially dramatic cardiorespiratory consequences of laryngeal chemoreflexes in newborns.…”
Section: Discussionmentioning
confidence: 97%
“…The experiments were conducted on 17 preterm lambs (8 control and 9 nCPAP of 6 cmH 2 O) born 14 days prematurely as previously described (8). Briefly, premature labor was induced by mifepristone (8 mg/kg; Sigma-Aldrich, Oakville, Canada), after stimulation of lung surfactant maturation by intramuscular betamethasone (12 mg × 2; Schering-Plough Canada, Kirland, Canada).…”
Section: Animalsmentioning
confidence: 99%
“…This enhanced LCR-related cardiorespiratory inhibition in preterm lambs largely decreased with postnatal maturation (84), whereas the autonomic activity following LCR decreased (103). In addition, while application of nasal continuous positive airway pressure was found to consistently blunt the LCRrelated cardiorespiratory inhibition in preterm lambs, the overall effect of caffeine was found to be nonsignificant (85).…”
Section: Cardiorespiratory Events Originating From the Laryngeal Chemmentioning
confidence: 81%
“…Lambs require continuous care during the first 48h of life to prevent and treat hypothermia, hypoxia and hypoglycemia. In addition, high-flow nasal cannula is occasionally used in lambs with mild to moderate respiratory distress syndrome (85). Overall, our preterm lambs constitute a model of late preterm infant born at about 34 weeks of gestation.…”
Section: The Preterm Lamb Model To Study Cardiorespiratory Events Of mentioning
confidence: 99%